The Variety of Language in Kurdish Society - Hamaxarib, Shalaw S.; Saeed, Youssef Sh. (Humanities Journal of University of Zakho, 2017)
This research specializes for talking and analyze about the difference and variety of; language which is importance and research on it in context of sociolingustics. The research is trying to answer the following two questions: Is the variety of languge as phenomenon in all language socities is same? What are the reasons that cause of appearing and becoming of variety in Kurdish society in modality? The content of the research contains of two parts, introduction and result in the first part the variety of language described and focused on concept and variety of languge terms in different viewpoint of linguistics special in classify and factor of appearing and becoming language variety. In the second part which is explain about the factors of appearing in the language variety in Kurdish society with suitable examples. In the end, the importance result of the research and sources were recorded.